Palabras de Lin Yutang: Realismo e Idealismo, entre la Tragedia y la Comedia de la Vida. - Hoffman, Betsabé (Humania del Sur: Revista de Estudios Latinoamericanos, Africanos y Asiáticos)
The philosophies of Taoism and Confucianism based themselves on primitive Chinese thought. Chinese philosophy arose during an era of leisure, when priorities were other than ours. But we are all equal under the skin and hence what touched the human heart three thousand years ago continues to touch it today, and what touches the heart of a Chinese also touches the heart of a Westerner. What changes is the how we manage joy, but in particular, how we handle anguish and sadness. In sum, what makes us diff erent is the way we understand life and our capacity to enjoy it.